Street RABV Induces the Cholinergic Anti-inflammatory Pathway in Human Monocyte-Derived Macrophages by Binding to nAChr α7 - Embregts, Carmen W. E.; Begeman, Lineke; Voesenek, Cees J.; Martina, Byron E. E.; Koopmans, Marion P. G.; Kuiken, Thijs; GeurtsvanKessel, Corine H. (Frontiers in Immunology, 2021)
Rabies virus (RABV) is able to reach the central nervous system (CNS) without triggering a strong immune response, using multiple mechanisms to evade and suppress the host immune system. After infection via a bite or scratch from a rabid animal, RABV comes into contact with macrophages, which are the first antigen-presenting cells (APCs) that are recruited to the area and play an essential role in the onset of a specific immune response. It is poorly understood how RABV affects macrophages, and if the interaction contributes to the observed immune suppression. This study was undertaken to characterize the interactions between RABV and human monocyte-derived macrophages (MDMs). We showed that street RABV does not replicate in human MDMs. Using a recombinant trimeric RABV glycoprotein (rRABV-tG) we showed binding to the nicotinic acetylcholine receptor alpha 7 (nAChr ɑ7) on MDMs, and confirmed the specificity using the nAChr ɑ7 antagonist alpha-bungarotoxin (ɑ-BTX). We found that this binding induced the cholinergic anti-inflammatory pathway (CAP), characterized by a significant decrease in tumor necrosis factor ɑ (TNF-ɑ) upon LPS challenge. Using confocal microscopy we found that induction of the CAP is associated with significant cytoplasmic retention of nuclear factor κB (NF-κB). Co-cultures of human MDMs exposed to street RABV and autologous T cells further revealed that the observed suppression of MDMs might affect their function as T cell activators as well, as we found a significant decrease in proliferation of CD8+ T cells and an increased production of the anti-inflammatory cytokine IL-10. Lastly, using flow cytometric analysis we observed a significant increase in expression of the M2-c surface marker CD163, hinting that street RABV might be able to affect macrophage polarization. Taken together, these results show that street RABV is capable of inducing an anti-inflammatory state in human macrophages, possibly affecting T cell functioning.